Penegakan Hukum terhadap Pelaku Tindak Pidana Penipuan : Studi Putusan Nomor: 99/Pid.B/2024/PN TJK - Ardinia Awanis Shabrina; Tami Rusli; Suta Ramadan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The crime of fraud is a form of crime that not only causes material loss, but also has an impact on the intangible losses experienced by the victim, such as loss of sense of security, trust, and social stability. Fraud also has the potential to disrupt public order and reduce public trust in the legal system. Therefore, law enforcement against this criminal act is an important aspect in maintaining legal certainty and a sense of justice. This study aims to analyze the form of law enforcement against perpetrators of fraud crimes by focusing on the factors that cause perpetrators to commit fraud and the judge's considerations in imposing judgments. The case studied refers to Decision Number: 99/Pid.B/2024/PN.Tjk. The research method uses a normative juridical approach, by examining laws and regulations, legal doctrines, and case studies through the analysis of court decisions. The results of the study show that the legal provisions regarding fraud have been regulated in Article 378 of the Criminal Code (KUHP). However, implementation in the field is often constrained by limited evidence, the increasingly diverse modus operandi of perpetrators, and low legal awareness of the public. The judge in considering the verdict not only pays attention to the juridical aspect, but also takes into account the social and psychological impact on the victim. As a recommendation, this study emphasizes the importance of increasing coordination between law enforcement officials to strengthen the investigation and evidence process. The use of digital technology, especially in the collection of electronic evidence, is a strategic step in dealing with modern fraud modes. In addition, legal education to the public needs to be improved to foster legal awareness and prevent fraud crimes in the future.